The Effect of Muscle Length of the Inferior Head of the Lateral Pterygoid Muscle on the Frequency of EMG Power Spectrum - Nishizaki, Hiroshi; Kawano, Akira; Uchida, Shinji; Inoue, Hiroshi; Takahashi, Reitaro; Maeda, Teruta; Kanehira, Harukazu; Nishiura, Kazunori (Nihon Hotetsu Shika Gakkai Zasshi, 1991)
Six male subjects were studied to determine the effect on the EMG power spectra of shortening the inferior head of the lateral pterygoid muscle (ILPt) during isometric protrusive and lateral protrusive contraction at three different muscle lengths. Among all muscle lengths, no significant difference in mean frequency of EMG power spectra was seen on either side of the ILPt during isometric protrusive contraction, or on the contralateral side of the ILPt during isometric lateral protrusive contraction. This result is similar to that for the digastric muscle during isometric under opening at various jaw positions, but differs from those for the temporalis and masseter muscles at during isometric clenching at various jaw positions. It was speculated that this lack of significant mean frequency change at different muscle lengths is characteristic of the EMGs of jaw depressor muscles.